1995
DOI: 10.1074/jbc.270.20.11851
|View full text |Cite
|
Sign up to set email alerts
|

The Asparagine-linked Oligosaccharides of the Human Chorionic Gonadotropin β Subunit Facilitate Correct Disulfide Bond Pairing

Abstract: The role of asparagine (N)-linked oligosaccharide chains in intracellular folding of the human chorionic gonadotropin (hCG)-beta subunit was determined by examining the kinetics of folding in Chinese hamster ovary (CHO) cells transfected with wild-type or mutant hCG-beta genes lacking one or both of the asparagine glycosylation sites. The half-time for folding of p beta 1 into p beta 2, the rate-determining step in beta folding, was 7 min for wild-type beta but 33 min for beta lacking both N-linked glycans. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…Our analysis of the importance of the carbohydrate moieties in the binding of PR3 to Wegener's autoantibodies clearly shows that autoantibody recognition of PR3 epitope(s) is mainly oligosaccharide-independent in PMN-derived PR3, which already has a proper folding. Glycosylation, however, may also be involved in the folding process of PR3 as suggested by other reports showing that the N-linked oligosaccharides and their processing are critical for proper glycoprotein folding and assembly [27].…”
Section: Different Wg Sera and Gave Similar Resultsmentioning
confidence: 89%
“…Our analysis of the importance of the carbohydrate moieties in the binding of PR3 to Wegener's autoantibodies clearly shows that autoantibody recognition of PR3 epitope(s) is mainly oligosaccharide-independent in PMN-derived PR3, which already has a proper folding. Glycosylation, however, may also be involved in the folding process of PR3 as suggested by other reports showing that the N-linked oligosaccharides and their processing are critical for proper glycoprotein folding and assembly [27].…”
Section: Different Wg Sera and Gave Similar Resultsmentioning
confidence: 89%
“…23 It is also consistent with the role of glycosylation of the CK domains in Muc2 and human chorionic gonadotrophin which similarly affect dimer formation. 33,34 It is not known precisely how glycosylation promotes dimer formation but in the case of the Muc2, dimers were shown to form at an increased rate, but to be less stable and to rapidly revert to monomers. 33 It has been demonstrated that core glycan residues can interact with neighbouring amino acids and decrease flexibility of the local peptide region, stabilizing the protein structure.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of hCG elucidates that both the A and the β subunits contain unusual cystine-knot structures, involving three disulphide bridges each [26]. In addition, single-chain hCG contains four Nlinked sugars that are essential for intracellular folding and transport, as well as for biological activity [4]. Since functional single-chain hCG can be produced by Dictyostelium,we conclude that this organism contains a large variety of chaperones and folding enzymes, which are able to perform all post-translational modifications necessary for biological activity of glycoprotein hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Since both the A and the β subunits contain a so-called cystine knot, it can be anticipated that protein disulphide isomerase plays a key role in the facilitation of the folding process [3]. In addition, it has been shown that the N-linked oligosaccharide side chains are required for proper folding, disulphide formation and secretion of hCG [4].The gonadotropins have been expressed in Chinese Hamster Ovary (CHO) cells, and their recombinant derivatives have bioCorrespondence to P. D. J. …”
mentioning
confidence: 99%